Transcriptome profiling of hypothalamus-pituitary-ovary axis provides insights into egg-laying interval differences between european meat pigeons and shiqi pigeons - Wang, Xinlei; Yang, Liyu; Li, Ruiting; Zhang, Liheng; Han, Zhanbing; Wang, Runzhi; Li, Qiang; Zhang, Dingding; Yang, Mingjun; Yang, Pengkun (Frontiers in Genetics, 2025)
IntroductionThe long egg-laying interval of pigeons leads to low egg production, and the hypothalamus-pituitary-ovary (HPO) axis plays a crucial role in regulating the egg-laying process of poultry. European meat pigeons have a shorter egg-laying interval than Shiqi pigeons, but the molecular mechanism underlying this difference remains unclear.MethodsReproductive phenotypic data of 300 pairs of pigeons from each breed were collected for 6 months. Five 2-2.5-year-old female pigeons from each breed were selected, and their hypothalamus, pituitary, and ovary tissues were collected for transcriptome sequencing. Differentially Expressed Genes (DEGs) were identified, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed.ResultsThe egg-laying interval of European meat pigeons (32.76 ± 3.25 days) was significantly shorter than that of Shiqi pigeons (33.11 ± 3.86 days, P=0.024). A total of 39, 101, and 199 DEGs were identified in the comparisons of SH vs EH, SP vs EP, and SO vs EO, respectively. DEGs in the hypothalamus and pituitary were enriched in pathways such as thyroid hormone transport and calcium-mediated signaling; DEGs in the ovary were enriched in pathways such as embryonic development and steroid biosynthesis. The thyroid hormone signaling pathway (in the hypothalamus and pituitary) and the steroid hormone biosynthesis pathway (in the ovary) were significantly enriched, and key genes such as StAR, EYA1, HAND2, HOXB8, and NRN1 were identified.DiscussionThe hypothalamus-pituitary-ovary axis regulates the egg-laying interval of pigeons through tissue-specific pathways. Among them, the thyroid hormone signaling pathway controls upstream hormone secretion, and the steroid biosynthesis pathway affects follicle maturation. The identified key genes may serve as targets for shortening the egg-laying interval.